The istant changes of the salivary glands to stress - A. V. Gerasimov; S. V. Logvinov; V. P. Kostyuchenko (Бюллетень сибирской медицины, 2010)
Night lighting and microwave exposure have been influence on structures of stress realization. The endocrine, fotoperiodical and adaptive functions of rodent submandibular salivary glands belonging to hormone produced duct cells. To evaluate their morphofunctional state at guinea-pigs and rats using the methods of light and electron microscopy there have been analyzed striated and granular ducts. It has been revealed that instant and twenty-four-hour strengthening of duct cell stress induced secretory activity was similar. It is concluded that salivary glands take part in circadian expectations to stress.